Shen-Qi-Jie-Yu-Fang exerts effects on a rat model of postpartum depression by regulating inflammatory cytokines and CD4+CD25+ regulatory T cells - Li JY (Dove Medical Press, 2016)
Jingya Li,1,* Ruizhen Zhao,1,* Xiaoli Li,1 Wenjun Sun,1 Miao Qu,1 Qisheng Tang,1 Xinke Yang,1 Shujing Zhang2 1Third Affiliated Hospital, 2School of Basic Medical Sciences, Beijing University of Chinese Medicine, Beijing, People’s Republic of China *These authors contributed equally to this work Background: Shen-Qi-Jie-Yu-Fang (SJF) is composed of eight Chinese medicinal herbs. It is widely used in traditional Chinese medicine for treating postpartum depression (PPD). Previous studies have shown that SJF treats PPD through the neuroendocrine mechanism. Aim: To further investigate the effect of SJF on the immune system, including the inflammatory response system and CD4+CD25+ regulatory T (Treg) cells. Materials and methods: Sprague Dawley rats were used to create an animal model of PPD by inducing hormone-simulated pregnancy followed by hormone withdrawal. After hormone withdrawal, the PPD rats were treated with SJF or fluoxetine for 1, 2, and 4 weeks. Levels of Treg cells in peripheral blood were measured by flow cytometry analysis. Serum interleukin (IL)-1β and IL-6 were evaluated by enzyme-linked immunosorbent assay, and gene and protein expressions of IL-1RI, IL-6Rα, and gp130 in the hippocampus were observed by reverse-transcription polymerase chain reaction and Western blot. Results: Serum IL-1β in PPD rats increased at 2 weeks and declined from then on, while serum IL-6 increased at 1, 2, and 4 weeks. Both IL-1β and IL-6 were downregulated by SJF and fluoxetine. Changes in gene and protein expressions of IL-1RI and gp130 in PPD rats were consistent with changes in serum IL-1β, and were able to be regulated by SJF and fluoxetine. The levels of Treg cells were negatively correlated with serum IL-1β and IL-6, and were decreased in PPD rats. The levels of Treg cells were increased by SJF and fluoxetine. Conclusion: Dysfunction of proinflammatory cytokines and Tregs in different stages of PPD was attenuated by SJF and fluoxetine through the modulation of serum concentrations of IL-1β and IL-6, expressions of IL-1RI, and gp130 in the hippocampus, and CD4+CD25+ Treg cells in peripheral blood. Keywords: postpartum depression, inflammatory cytokines, antidepressant drugs, Chinese herbal medicine, shenqi jieyu fang, animal model